Longitudinal developmental trajectories of inhibition and white-matter maturation of the fronto-basal-ganglia circuits. (December 2022) - Singh, Mervyn; Skippen, Patrick; He, Jason; Thomson, Phoebe; Fuelscher, Ian; Caeyenberghs, Karen; Anderson, Vicki; Nicholson, Jan M.; Hyde, Christian; Silk, Timothy J.
Abstract: Response inhibition refers to the cancelling of planned (or restraining of ongoing) actions and is required in much of our everyday life. Response inhibition appears to improve dramatically in early development and plateau in adolescence. The fronto-basal-ganglia network has long been shown to predict individual differences in the ability to enact response inhibition. In the current study, we examined whether developmental trajectories of fiber-specific white matter properties of the fronto-basal-ganglia network was predictive of parallel developmental trajectories of response inhibition. 138 children aged 9–14 completed the stop-signal task (SST). A subsample of 73 children underwent high-angular resolution diffusion MRI data for up to three time points. Performance on the SST was assessed using a parametric race modelling approach. White matter organization of the fronto-basal-ganglia circuit was estimated using fixel-based analysis. Contrary to predictions, we did not find any significant associations between maturational trajectories of fronto-basal-ganglia white matter and developmental improvements in SST performance. Findings suggest that the development of white matter organization of the fronto-basal-ganglia and development of stopping performance follow distinct maturational trajectories. Highlights: Response inhibition and fronto-basal-ganglia white matter development was studied. Improvement in inhibition was driven by reduced variability and extreme responses. Bilateral fronto-basal-ganglia fiber cross-section increased with age. Fiber maturation in these pathways did not predict improvements in inhibition.